(untitled) (UNWE Yearbook, 2005)
In the last decade of the past century the Bulgarian industry entered a prolonged crisis due to complex internal and external factors typical of East European economies in transition. The new market realities, including those of an internationalized economy, introduced new challenges for the industry, mainly involving its competitiveness. By and large, it has not succeeded in dealing with these challenges.The emerging tendency of the country’s industrialization has brought forward a number of crucial issues.What is the potential of the industry and what shape the model of industry development should take in order to secure the increased competitiveness in view of the forthcoming accession of the country to the European Union? What industrial sectors, production facilities and products have an available market potential and competitive advantage?How can the state and the business oppose the competitiveness crisis in the industry and secure prerequisites and conditions to achieve and update competitive advantages and growth via a jointly developed and jointly pursued industrial policy? The paper seeks to address these complex issues. Its content is mainly targeted on pragmatic and applied aspects, including the state of the industry and its sectors, and aimed at outlining the approaches and tools geared to bolster and stimulate industrial growth.The industrial policy and more specifically, its main points of departure are viewed in terms of accelerating the processes of transition from a resource-intensive stage of industrial development to investment and innovation oriented stages of development.The paper also poses a number of problems, with the author’s arguments defending a certain stand, i.e. priorities in the industrial policy of the country, the ensuing support on the part of the state to meet the political targets, etc.